THE ENGLISH LITERACY PRACTICE, WORLD KNOWLEDGE PROFICIENCY, AND TEXT SKIMMING OF TENTH GRADES - Fadilla, Atika Nur; Ningrum, Ary Setya Budhi; Nurkholida, Erna (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
Literacy is vital in understanding pupils' knowledge of learning content. However, learners have encountered several learning challenges, including vocabulary mastering and reading comprehension. The purpose of this study was to see if there was a link between students' literacy practice, world knowledge proficiency, and text skimming in senior high school. This study's data was analyzed using quantitative methodologies and a correlation design. There were 141 tenth grade students from SMAN 4 Kota Kediri who took part. They completed the vocabulary and reading comprehension tests by multiple-choice questions and items for the reading habits questionnaire. The researcher utilized Pearson Product Moment Coefficient and using SPSS ver 26.0 for Windows to assess the correlation. Following data analysis, it was discovered that all variables have a significant (sig.) value of 0.00. while coefficient The correlation between reading literacy and vocabulary mastery was 0.504, whereas the correlation between reading literacy and text skimming was 0.257 and the correlation between vocabulary mastery and text skimming was 0.441. Based on the above results, there was a substantial connection between all variables, therefore Ho is rejected but Ha should be approved. When pupils have a high degree of reading literacy, it can be argued that they have a greater skill in vocabulary mastery and text skimming. The higher the degree of students' reading literacy and vocabulary knowledge, the better the students' reading comprehension ability.